(untitled) (Canadian Medical Education Journal, 2013)
Background: There is limited understanding of the impact of Triple C competency-based curriculums on the preparation of residents for family practice. This paper describes a competency-based curriculum within an integrated longitudinal block design and presents preliminary evaluation data on the impact of this curriculum on preparedness for family practice. Methods: First and second year family medicine residents were surveyed as a component of a year-end program evaluation to assess the extent to which the residency program is preparing them to engage in a variety of practice domains, the likelihood that they would engage in these domains, and the extent to which this residency program is comprehensive, relevant to their development as a family physician, and promotes interprofessional practice. Results: Residents perceived themselves as prepared to engage in most practice areas and their intentions to engage in various practice domains were positively correlated to their ratings of preparedness. Ratings reflected that residents perceived this program as comprehensive and relevant to their development as a family physician and they perceived a high degree of encouragement for interprofessional practice. Conclusions: This study provides some preliminary evidence that an integrated competency-based curriculum, with an emphasis on interprofessional practice has the potential to effectively prepare residents for practice in family medicine.